Pembentukkan Pusat Informasi dan Konseling Kesehatan Reproduksi Remaja (PIK-KRR) di SMPN 28 Kota Pekanbaru - Yanti; Lailiyana (Universitas Lancang Kuning, 2021)
Malnutrition in toddlers is still a health problem in Indonesia. Malnutrition generally occurs in children under age 5, because at this age, children experience rapid growth. It is estimated there are still around 1.7 million children under threat of malnutrition scattered throughout Indonesia. The purpose of this community service activity is to conduct training for cadres in maternal and child health service (posyandu) about the skills in giving MP-ASI counselling in Tanah Merah village, Siak Hulu Subdistrict, Kampar Regency in 2019. The method of this activity carried out disseminating information on community service activities in the village apparatus, providing material and the practice of counselling by cadres in maternal and child health service (Posyandu). The results of this community service activities were the socialization of community service activities to village officials, the Siak Hulu Health Center and Posyandu cadres in the village office hall, followed by the provision of material for four meetings. To assess the successful implementation of community service activities, a cadre practice was conducted on the Posyandu day. Based on the results of the pre and post-test evaluations, there was an increase in cadre knowledge about the MP-ASI material. It is recommended for Posyandu cadres to apply the results of the training by activating extension activities by cadres at table V every Posyandu opening day